Contribution of peripheral chemoreceptors to ventilation and the effects of their suppression on exercise tolerance in chronic heart failure. Issue 6 (December 1996) - Chua, T. P.; Ponikowski, P. P.; Harrington, D.; Chambers, J.; Coats, A. J.
Abstract : OBJECTIVES: To assess the contribution of peripheral chemoreceptors to ventilation and the effects of continuous inspired oxygen on exercise tolerance in chronic heart failure patients. The role of peripheral chemoreceptors in mediating hyperpnoea in chronic heart failure is unknown. Hyperoxia is known to suppress the peripheral chemoreceptor drive. The magnitude of decrease in ventilation with transient inhalations of oxygen thus provides a measure of the contribution of the peripheral chemoreceptors to ventilation. SETTING: Tertiary specialist hospital. SUBJECTS AND METHODS: Three breaths of 100% oxygen were given at rest and also during cycle ergometry at 25 W to 8 healthy controls (age 52.0 (4.7) (SEM) years) and 13 patients with chronic heart failure (age 60.5 (2.1) years (P = NS); radionuclide left ventricular ejection fraction 25.5 (4.3)%). The peripheral chemoreceptor sensitivity was also measured by assessing the ventilatory response to hypoxia using transient inhalations of pure nitrogen. Another group of 12 patients with chronic heart failure (age 65.5 (1.5) years; left ventricular ejection fraction 21.3 (3.0)%) underwent treadmill exercise testing on 2 occasions, breathing air or 100% oxygen in a randomised single-blind manner, to examine the effects of continuous inspired oxygen on exercise tolerance. RESULTS: The reduction in ventilation with transient hyperoxia was 18.1 (2.9)% v 17.9 (2.6)% (P = NS) at rest and 20.4 (2.8)% v 21.0 (1.6)% (P = NS) during cycle ergometry, for controls and patients respectively. The hypoxic chemosensitivity was higher in patients (0.232 (0.022) v 0.572 (0.082) 1/min/%SaO2; P = 0.002). Continuous inspired oxygen increased exercise time (517 (31) v 455 (27) seconds; P = 0.003), and a trend towards a reduction in the ventilatory response to exercise, characterised by the regression slope relating ventilation to carbon dioxide output, was evident (31.27 (2.60) v 34.19 (2.35); P = 0.08). CONCLUSIONS: Despite an increased peripheral chemoreceptor sensitivity, the proportionate contribution of peripheral chemoreceptors to ventilation remained similar in heart failure patients (about 20%). This suggests that the peripheral chemoreceptors are not the main mediator of increased ventilation and there are other non-peripheral chemoreceptor-mediated mechanisms involved. Hyperoxia reduced ventilation at rest and during cycle ergometry. The increase in exercise duration with continuous inspired oxygen that was associated with a reduction in exercise ventilatory response suggests that suppression of the peripheral chemoreceptors may improve exercise tolerance; the effects of possible reduced skeletal muscle anaerobiosis cannot be excluded, however.